UNDERSTANDING HOW THE IMPLEMENTATION OF THE SPECIALIST HIGH SKILLS MAJOR PROGRAM CONTRIBUTES TO STUDENT OUTCOMES - Segedin, Lauren (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2018)
The Specialist High Skills Majors (SHSM) program has been implemented in Ontario as a way to increase secondary graduation rates. This study’s aim was to understand how the implementation of the SHSM program impacts student outcomes. The conceptual framework consists of an amended version of Fullan’s (2007) critical factors that affect policy implementation. The study’s methods analyzed provincial student achievement data. Thirty-four interviews from four school districts in Ontario occurred. A true need, program clarity and simplicity, equality of resources, and strong leadership were found to affect program implementation, and in turn, student outcomes.